Novel surgical techniques in female to male gender confirming surgery - Djordjevic, Miroslav L. (Translational Andrology and Urology, 2018)
The current management of female to male (FTM) gender confirmation surgery is based on the advances in neo phalloplasty, perioperative care and the knowledge of the female genital anatomy, as well as the changes that occur to this anatomy with preoperative hormonal changes in transgender population. Reconstruction of the neophallus is one of the most difficult elements in surgical treatment of female transsexuals. While there is a variety of available surgical techniques, their results are not equally acceptable to all patients. The preference for a particular surgical technique mostly depends on the patient’s desires and expectations. Nevertheless, the surgeon’s duty is to fully inform the patient about all the advantages and disadvantages, as well as all complications that might occur after surgical procedure—and even to talk them out of a desired surgical technique if there are contraindications. Metoidioplasty is a technically demanding surgical procedure used in FTM transsexuals who desire a gender reassignment surgery (GRS) without undergoing a complex, multi-staged surgical creation of an adult-sized phallus. Metoidioplasty is viable in cases where the clitoris seems large enough after androgen hormonal treatment. Since the clitoris plays the main role in female sexual satisfaction, its impact on the outcome of FTM transgender surgery is predictable. Various free flaps have been reported for total phalloplasty, such as radial forearm flap, latissimus dorsi flap, anterolateral tight flap, different abdominal wall flaps, free deltoid flap, scapular free flap, sensate osteocutaneous free fibula flap, tensor fasciae latae, deep epigastric artery perforator flap and dorsalis pedis flap. The fact that there are so many techniques for penile reconstruction in cases of penis absence, proves that none of the above mentioned techniques succeeded in achieving the ideal goals of penis reconstruction. We will emphasize the most commonly used surgical techniques in genital confirmation in FTM transsexuals with reference to respective eligibility criteria for each procedure.